Role of genetic variations of abc (abcb1, abcc1 and abcg2) on triple negative breast cancer susceptibility risk - Ing, Yeoh Hao (2024)
Triple-negative breast cancer (TNBC) is known for its aggressive behaviour and is associated with poor prognosis. ABC transporter genes were widely studied for their association with multiple drug resistance in cancer patients and other diseases. However, the evidence on ABC transporter gene polymorphisms and TNBC susceptibility remains limited and inconclusive. The main objective of this study was to investigate the association of ABC transporter genes ABCB1, ABCC1, and ABCG2 polymorphisms with TNBC susceptibility in the Malaysian population. This case-control study was conducted at Hospital Universiti Sains Malaysia, Kubang Kerian, Kelantan. A volume of three mL of peripheral blood samples were collected from 79 TNBC patients and 100 healthy controls, followed by genomic DNA extraction from the blood. Next, the genotyping was performed by employing polymerase chain reaction-restriction fragment length polymorphisms (PCR-RFLP) using enzymes such as TaaI, BseMI, RsaI, EcoO1091, MboI and PspF1 as well as amplification-refractory mutation system-polymerase chain reaction (ARMS-PCR) methods. The genotypes were examined by observing the band sizes of digested fragments and PCR products on 3% agarose gel through electrophoresis. The allele, genotype and haplotype of polymorphisms were evaluated, and the independent χ2 test was carried out to elucidate their association with TNBC susceptibility and other clinicopathological variables while the logistic regression was performed to measure the strength of association. The allele and genotype analysis showed that the T allele and TT genotype carrier of ABCB1 1236 C>T were associated with the increased risk of TNBC susceptibility (p = 0.026 and 0.035, respectively) with OR of 1.628 (95% CI: 1.060-2.501) and 3.034 (95% CI: 1.171-7.866) respectively. Besides, ABCG2 421 C>A was also associated with the advanced staging of the tumour (p = 0.004) and the OR for the A allele and AA genotype carrier was 3.464 (95% CI: 1.687-7.111) and 11.625 (95% CI: 2.187-61.804) respectively. Likewise, a significant association was also observed in the AA genotype carrier of ABCG2 421 C>A with rarer histologic subtypes of metaplastic and medullary carcinoma (p = 0.016), with an OR of 6.171 (95% CI: 1.467-25.961). Meanwhile, the haplotype analysis demonstrated a significant association between the ABCB1 1236C/3435T/2677G carrier and TNBC susceptibility (p = 0.011), showing the protective effect with reduced OR of 0.120 (95% CI: 0.015-0.952). Besides, the haplotype carrier of ABCG2 34G/421A was associated with an increased risk of advanced staging (p = 0.030, OR: 2.333, 95% CI: 1.005-5.417) and rarer histologic type of metaplastic and medullary carcinoma (p = 0.009, OR: 2.599, 95% CI: 1.027-6.576). In conclusion, the present study suggests that ABCB1 and ABCG2 polymorphisms were associated with TNBC susceptibility, advanced staging, and rarer histologic types of carcinomas. This study supports the hypothesis that selected variants in ABC transporter genes contribute to TNBC susceptibility risk and could be considered candidate biomarkers and prognostic factors in TNBC management.